Estimation of Phenolic and Flavonoid Compounds and Antioxidant Activity of Spent Coffee and Black Tea (Processing) Waste for Potential Recovery and Reuse in Sudan - Samar A. Abdeltaif; Khitma A. SirElkhatim; Amro B. Hassan (Recycling, 2018)
This study aimed to evaluate the antioxidant power associated with spent coffee and black tea processing waste. Ethanolic extracts from the samples were prepared in order to determine the quantities/concentrations of the phenolic and flavonoid compounds, polyphenols, and associated levels of antioxidant activity. The results showed that both the spent coffee and black tea waste had high amounts of phenolic compounds and high antioxidant activity rates. The total phenolic and flavonoids content was found to be significantly higher (p < 0.05) in the spent black tea than in the spent coffee. The total phenolic content was found to be 152.8 and 97.87 mg of gallic acid equivalent/g, while the total amount of flavonoids was found to be 47.40 and 34.32 mg catechin/g in spent black tea and coffee, respectively. However, the spent coffee had a significantly higher (p < 0.05) antioxidant activity than that detected in the spent black tea (57.83%). Consequently, the results revealed that the waste residue of spent coffee and black tea may be considered as natural sources of bioactive compounds and that there may be potential for recycling these waste products, which could be applied in different industries to further develop functional foods.